Evaluation as category of modern phraseology - Сизонов, Дмитро Юрійович (Київський національний університет імені Тараса Шевченка, 2018)
The article analyzes the category of evaluation as dominant characteristics of modern phraseology. A wide range of scientific views on evaluation within the framework of new linguistic directions (media linguistics, legal linguistics, suggestive linguistics, political linguistics, psycholinguistics etc.) is considered. The immanence of evaluation in modern linguistics has become particularly relevant in the theory of functionalism, where the evaluation of a phraseologism is judged as not an optional feature, but one which underlies its semantics. The evaluation, accordingly, is considered with respect to the initial emotional-expressive connotation of a phraseologism. It is proved that value parameters of phraseology are laid down in its communicative essence, as any phraseologism a priori carries some sort of evaluation. If we regard evaluation as an oppositional set of value orientations (good / evil, beautiful / ugly, interesting / uninteresting, many / few, etc.), we can define a phraseologism as a verbalized form of such oppositions in the communication process. Logically, when creating new phraseologisms (e.g. in mass communication) it is the category of evaluation that determines the vector of functioning of phraseology. Hence, media phraseology is a mirror image of sentiments and value beliefs of a certain society and is relevant in the time frame (which is an extralinguistic characteristics of a media phraseologism and a basis for its further functioning and mass reproduction). We have proven that phraseological evaluation is influenced by extralinguistic factors such as politics, culture, information technologies, etc. The emergence of a new phraseology is the result of evaluative reconsideration of traditional linguistic forms of certain industries – sports, arts, medicine, education, etc. Consequently, evaluation is a universal category of a phraseologism, considering the fact of formation of society’s values through language phenomena. The axiology of each phraseologism is determined in social parameters, where media remains the main tool for the retransmission of society’s value orientations through the means of language, the main of which are phraseologisms.

У статті аналізується категорія оцінності як домінантної характеристики сучасної фразеології. Розглядається широкий спектр наукових поглядів на оцінку в межах неонапрямків лінгвістики – медіа- та юрислінгвістики, сугестивної та політичної лінгвістики, психолінгвістики та ін. Аналіз іманентності оцінки в сучасній лінгвістиці набув особливої актуальності в теорії функціоналізму: оцінність фразеологізма – не факультативна ознака, а така, що лежить в основі його семантики. Оцінка, відповідно, розглядається з урахуванням початкового емоційно-експресивного забарвлення фразеологізма. Доведено, що ціннісні параметри фразеології закладені в її комунікативній сутності, адже фразеологізм a priori несе в собі якусь оцінку. Якщо розглядати оцінність як опозиційний комплекс ціннісних орієнтирів (добро / зло, красивий / некрасивий, цікавий / нецікавий, багато / мало та ін.), то фразеологізм визначається як вербалізована форма таких опозицій у процесі комунікації. Логічно, що при творенні нових фразеологізмів, напр., у масовій комунікації, саме оцінка визначає вектор функціонування фразеології. Медійна фразеологія, таким чином, є дзеркальним відображенням настроїв суспільства, його ціннісних переконань та актуальною в часових рамках (це є водночас екстралінгвальною характеристикою медіафразеологізма й основою для його подальшого функціонування та масового тиражування). Нами доведено, що на фразеологічну оцінність впливають такі позамовні фактори, як політика, культура, інформаційні технології та ін., а також наслідки мовної комунікації в новий час. Поява нової фразеології є також результатом оцінного переосмислення усталених мовних форм певних галузей – спортивної, мистецької, медичної, освітньої та ін. Отже, оцінність є універсальною характеристикою фразеологізма, якщо враховувати факт формування цінностей суспільства через мовні явища. Аксіологічність кожного фразеологізма визначається в соціальних параметрах, де медіа залишаються головним інструментом для ретрансляції ціннісних орієнтирів суспільства засобами мови, зокрема і фразеологізмами.
Оцінність як категорія сучасної фразеології
Keywords: phraseologism / idiom; functional linguistics; evaluation; axiology; modern Ukrainian language.; фразеологізм; функціональна стилістика; оцінність; аксіологічність; сучасна українська мова.